2001
DOI: 10.1159/000050769
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome in Spain, 1985–1997: Epidemiological and Public Health Views

Abstract: Retrospective demographic information and hospital record data were collected for 337 patients resident in Spain who had validated Guillain-Barré syndrome (GBS) diagnoses and clinical onset during the period 1985–1997 and had been admitted to 11 centres, covering a population of 3.9 million. The European age-adjusted GBS incidence per 100,000 for 1985–1997 among the population aged 20 and over was 0.85, with a breakdown of 1.14 in men and 0.58 in women. Incidence increased with age and time, with occasional ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
(34 reference statements)
4
20
0
3
Order By: Relevance
“…In the majority of studies that included incidence rates broken down by age, increases in rates were observed in most studies of people aged 50 years or more [11, 17, 22, 26, 31-33, 35-39, 46-49] , with some showing a decrease in the highest age group of 6 80 years [22,26,31,[35][36][37][38][47][48][49] .…”
Section: Variation With Agementioning
confidence: 99%
“…In the majority of studies that included incidence rates broken down by age, increases in rates were observed in most studies of people aged 50 years or more [11, 17, 22, 26, 31-33, 35-39, 46-49] , with some showing a decrease in the highest age group of 6 80 years [22,26,31,[35][36][37][38][47][48][49] .…”
Section: Variation With Agementioning
confidence: 99%
“…Bizim çalışmamızda da kış aylarında başvuran hasta sayısı daha fazla olmasına karşın bu fark istatistiksel olarak anlamlı değildi. Önceki çalışmalarda son 6 hafta içinde öncül enfeksiyon oranı %40-70 arasında bildirilmiştir [17,18]. Bizim çalışmamız-da da önceki çalışmalarla uyumlu bir şekilde en sık ÜSYE ve gastroenterit olmak üzere hastaların % 63.9'sinde öncül enfeksiyon mevcuttu.…”
Section: Discussionunclassified
“…Češće se javlja kod osoba muškog pola i u starosnoj dobi od 50 do 80 godina (3)(4)(5). Razvoju GBS najčešće prethodi respiratorna ili gastrointestinalna infekcija, koja se registruje od tri dana do nekoliko nedelja prije početka neurološke simptomatologije (6).…”
Section: Uvodunclassified
“…U skladu sa ovim podacima su i rezultati prethodnih istraživanja o GBS (9,13). Prosječna starost naših pacijenata je bila oko 57,0 ± 15,9 godina, što je u skladu sa rezultatima iz prethodnih radova (4,14).…”
Section: Rezultatiunclassified